The politeness strategies employed by Asian and Western social media influencers - Noor Azam, Nur Qamarina; Badaruddin, Zuraidar; Ismail, Marina; Rashid Ali, Farrah Diebaa; Md Supie, Hawa Syamsina (UiTM Press, 2024)
Politeness strategies play a vital role in communication in order to avoid any conflicts or offending other people’s feelings. Showing good manners and uttering good words are extremely important in Islam. This is in line with the Prophet Muhammad’s teaching for his followers to be kind and speak compassionately. In communication, conflicts may occur due to misunderstanding and misinterpreting especially when communicating inter-culturally. The Prophet Muhammad advised us to speak beneficently or keep silent (Muslim & Bukhari). Therefore, the use of politeness in communication is important to bridge good social communication between speakers. However, different cultures may have different strategies and different interpretations of the concepts of politeness strategy in communication. Hence, this study aimed to identify the types of politeness strategies as well as the most dominant strategies employed by ten selected Asian and Western social media influencers. This study also highlighted the differences and similarities of politeness strategies between two different cultures in social media. The data - the influencers’ Instagram captions were analysed using qualitative method and classified according to Brown and Levinson's (1987) politeness theory. The results indicated that positive politeness strategies are the most dominant strategies employed by Asian and Western social media influencers compared to negative politeness strategies, off-record strategies and bald on-record strategies. Hence, this study showed that the influencers practised good manners and kind words in their online communication with the public as preached by the Prophet Muhammad. This research hopes to highlight the importance of politeness strategies and the effects of the strategies on communication.